Improving the mental health system for trauma victims in France. Issue 1 (31st December 2019) - El-Hage, Wissam; Birmes, Philippe; Jehel, Louis; Ferreri, Florian; Benoit, Michel; Vidailhet, Pierre; Prieto, Nathalie; François, Irène; Baubet, Thierry; Vaiva, Guillaume
ABSTRACT: France has a rich history of exposure to large-scale traumas such as wars, disasters and terrorist attacks, and psychiatric teams specialized in emergency interventions for mass trauma have been created across the territory. However, no public resources are dedicated for long-term interventions or for individual trauma cases. This letter describes how a government supported model of care has been created and implemented in 2019. A national centre for resources and resilience (CN2R) and 10 regional ambulatory services specializing in psychotraumatology were created with the aim of improving public mental health-care delivery while providing a comprehensive suite of services for trauma victims from the most immediate to longer-term considerations. HIGHLIGHTS: France opens a national centre for resources and resilience and 10 regional psychotraumatology centres. These facilities aim to ensure easy public access to specialized trauma care to all victims regardless of trauma type or individual victims' characteristics. The challenge is to achieve universal access to prevention, improve free access to trauma-focused psychotherapies, and ensure coordination of trauma care and social support.